2023
DOI: 10.1002/biot.202300240
|View full text |Cite
|
Sign up to set email alerts
|

Improving ribonucleic acid production in Saccharomyces pastorianus via in silico genome‐scale metabolic network model

Abstract: Ribonucleic acid (RNA) and its degradation products are important biomolecules widely used in the food and pharmaceutical industries for their flavoring and nutritional functions. In this study, we used a genome‐scale metabolic network model (GSMM) to explore genetic targets for nucleic acid synthesis in a Saccharomyces pastorianus strain (G03). Yeast 8.5.0 was used as the base model, which accurately predicted G03's growth. Using OptForce, we found that overexpression of ARO8 and ATP1 among six different stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The Yeast Consensus Model (Yeast8) provides a highly curated and comprehensive representation of yeast metabolism ( 23 , 25 ) and has been used as a template to reconstruct the draft genome-scale metabolic model of S. pastorianus . The reactions in Yeast8 that are present/absent in S. pastorianus were identified based on the presence/absence of the genes that support these reactions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Yeast Consensus Model (Yeast8) provides a highly curated and comprehensive representation of yeast metabolism ( 23 , 25 ) and has been used as a template to reconstruct the draft genome-scale metabolic model of S. pastorianus . The reactions in Yeast8 that are present/absent in S. pastorianus were identified based on the presence/absence of the genes that support these reactions.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, although the sequence of S. cerevisiae genome has been available for almost 30 years, only more recently the hybrid genomes of some S. pastorianus strains have been sequenced and annotated ( 10 , 12 , 18 22 ). It has been shown that S. pastorianus and S. cerevisiae exhibit significant differences in gene expression and metabolic levels, and that the Yeast8 model could not always accurately calculate the metabolic flux of S. pastorianus ( 23 ), hence the need to develop a model specific for S. pastorianus .…”
Section: Introductionmentioning
confidence: 99%
“…Construction of efficient cell factories requires extensive rewiring cellular metabolism toward overproduction of target metabolites through enzyme and metabolic engineering. [ 6,10–12 ] Rational engineering the biosynthetic pathways is considered to be the first step to improve chemical production. [ 3–6,13 ] Recently, several advanced metabolic engineering strategies were developed to enhance the biosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…The extent of cell membrane disruption can be adjusted depending on the specific application, requiring reversible or irre-versible membrane disruption. For example, reversible electroporation is used in ribonucleic acid production (RNA) in yeast, [12] as well as a tool for cell electrofusion for the production of monoclonal antibodies. [13] The versatility of the electroporation technique renders it a potent tool in genetic engineering, the food industry, as well as in medical applications [14,15] .…”
Section: Introductionmentioning
confidence: 99%